(untitled) (Journal of Health, Population and Nutrition, 2010)
The study describes the characteristics of maternal deaths in the city of Rio de Janeiro, Brazil, during 2000-2003. After investigation by public-health services, 217 maternal deaths were identified among predominantly non-white (48.9%), single (57.1%) women aged 29.6±7.3 years on average. Direct obstetric causes corresponded to 77.4% of the maternal deaths, mainly due to hypertensive disorders. HIV-related diseases accounted for 4% of the maternal deaths. Almost three-fourths of the mothers who died were aged 20-39 years, although the highest risk of maternal death corresponded to the age-group of 40-49 years (248.9 per 100,000 livebirths). The socioeconomic and demographic profiles of maternal deaths in the city of Rio de Janeiro reflected a vulnerable social situation. Appropriate interventions aimed at reducing maternal mortality need to encompass all women of childbearing age, irrespective of the magnitude of the risk of maternal death. Key words: Causes of death; HIV; Hypertensive disorders; Maternal health; Maternal mortality; Vital statistics; Women’s health; Brazil DOI: 10.3329/jhpn.v27i6.4331 J Health Popul Nutr 2009 Dec; 27(6): 794-801